2021
DOI: 10.1155/2021/4883509
|View full text |Cite|
|
Sign up to set email alerts
|

miR-381-3p Involves in Glioma Progression by Suppressing Tumor-Promoter Factor ANTXR1

Abstract: Accumulating studies revealed association between development of glioma and miRNA dysregulation. A case in point is miR-381-3p, but its mechanism in glioma is unclear yet. In this work, we confirmed that overexpressed miR-381-3p repressed biological functions of glioma cells. Additionally, we also discovered that upregulated anthrax toxin receptor 1 (ANTXR1) was negatively mediated by miR-381-3p. We further proved that miR-381-3p-targeted ANTXR1 was able to counteract the suppression of miR-381-3p on biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have shown the suppressive role of miR-381 (hsa-miR-381-3p) in cell metastasis and EMT in glioblastoma due to the suppression of LEF1 expression. In another study this miRNA inhibited malignant behavior of glioma cells by targeting ANTXR1 [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the suppressive role of miR-381 (hsa-miR-381-3p) in cell metastasis and EMT in glioblastoma due to the suppression of LEF1 expression. In another study this miRNA inhibited malignant behavior of glioma cells by targeting ANTXR1 [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%